Process of concept art creations with integration of 3D and 2D assets for animations - Dk Hannan Nabilah, Pg Hj Halidi (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The use of 3D models into 2D to create concept arts as a method has recently become popular that the need to find a standard method to integrate 3D assets into 2D to create concept art becomes the foundation of this thesis. Research has shown that more professional concept artists in the visual arts entertainment industry are favouring the utilizing 3 D assets in their workflow. The study aims to analyse, compare and differentiate the process of concept art creations made by different professionals of the industry that integrates 3D assets. The different combinations of steps will then be experimented together. Building on existing work on concept art creations, the research questions the process of concept art creation with integration of 3D assets, the commonly used steps taken and considerations needed for the workflow. With respect to literature review on concept arts, the method to approach the research is through observation, analysis with a question framework and experimentation with a structured defined process based on the artists. The professional artists observed were of different backgrounds and strengths in terms of concept art rendering. Both experiments successfully followed the defined process and resulted in ease concept art production in different methods and quality end results. However, the standard method of concept art creation designed in this research is narrowed to only environmental concept art and, on this basis, it is recommended that this is for environment concept art. Further research is needed to align with other concept arts creations.